The Past and Future of Nursing Research - Margaret M. Heitkemper, PhD, RN, FAAN (Elsevier, 2007)
The past three decades have witnessed a remarkable growth in nursing science development. In both Korea and the United States, nurse scientists are poised to address important issues related to the prevention and management of significant health care problems. The need for greater nursing science development in the areas of self management, genetics, geriatrics, health promotion across the lifespan, technology, and mental health are briefly highlighted. Future research efforts will be enhanced by interdisciplinary collaboration and the creation of international nursing research centers. At the same time, we need to remain cognizant of the importance of mentoring future nurse scientists.